2007
DOI: 10.1136/bjo.2007.128157
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X inactivation in an X linked nystagmus family resulted from a novel, p.R229G, missense mutation in the FRMD7 gene

Abstract: Aims: This study aimed to identify the underlying genetic defect of a large Turkish X linked nystagmus (NYS) family. Methods: Both Xp11 and Xq26 loci were tested by linkage analysis. The 12 exons and intron-exon junctions of the FRMD7 gene were screened by direct sequencing. X chromosome inactivation analysis was performed by enzymatic predigestion of DNA with a methylationsensitive enzyme, followed by PCR of the polymorphic CAG repeat of the androgen receptor gene. Results: The family contained 162 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…At least six genetic loci for CMN have been suggested, including three loci for autosomal dominant CMN (NYS2, MIM 164100, 6p12;NYS3, MIM 608345, 7p11;NYS4, MIM 193003, 13q) (Kerrison et al 1996;Klein et al 1998;Patton et al 1993;Ragge et al 2003) and three loci for X-linked CMN (NYS1, MIM 310700, Xq26-q27;NYS5, MIM 300589, Xp11.4-11.3;NYS6, MIM 300814, Xp22.3) (Cabot et al 1999;Kerrison et al 1999;Liu et al 2007). Mutation in FRMD7 has been identiWed as the most common cause of X-linked CMN (He et al 2008;Kaplan et al 2008;Schorderet et al 2007;Self et al 2007;Shiels et al 2007;Tarpey et al 2006;Zhang et al 2007a, b). In large families with CMN, the condition is usually transmitted as an X-linked trait, but is occasionally reported as an autosomal dominant trait, which has hindered the search for additional loci and genes.…”
Section: Introductionmentioning
confidence: 99%
“…At least six genetic loci for CMN have been suggested, including three loci for autosomal dominant CMN (NYS2, MIM 164100, 6p12;NYS3, MIM 608345, 7p11;NYS4, MIM 193003, 13q) (Kerrison et al 1996;Klein et al 1998;Patton et al 1993;Ragge et al 2003) and three loci for X-linked CMN (NYS1, MIM 310700, Xq26-q27;NYS5, MIM 300589, Xp11.4-11.3;NYS6, MIM 300814, Xp22.3) (Cabot et al 1999;Kerrison et al 1999;Liu et al 2007). Mutation in FRMD7 has been identiWed as the most common cause of X-linked CMN (He et al 2008;Kaplan et al 2008;Schorderet et al 2007;Self et al 2007;Shiels et al 2007;Tarpey et al 2006;Zhang et al 2007a, b). In large families with CMN, the condition is usually transmitted as an X-linked trait, but is occasionally reported as an autosomal dominant trait, which has hindered the search for additional loci and genes.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved ezrin/radixin/ moesin (ERM) proteins often organize membranecytoskeletal interactions (Tsukita and Yonemura, 1999), and share a C-terminal actin-binding domain and an N-terminal FERM domain that binds membrane proteins (Mcclatchey and Fehon, 2009), also acting as scaffolding for adaptor and signaling molecules (Mcclatchey and Fehon, 2009). (Tarpey et al, 2006;Schorderet et al, 2007;Self et al, 2007;Shiels et al, 2007;Zhang B. et al, 2007;He et al, 2008a;Kaplan et al, 2008;Li et al, 2008a;Du et al, 2011;Khan et al, 2011;Thomas et al, 2011;Hu et al, 2012;Radhakrishna et al, 2012) and the novel mutation in this study within FRMD7 has been indicated (Note: for interpretation of the references to color in this figure legend, the reader is referred to the web version of this article)…”
Section: Discussionmentioning
confidence: 90%
“…3) (Tarpey et al, 2006;Schorderet et al, 2007;Self et al, 2007;Shiels et al, 2007;Zhang B. et al, 2007;He et al, 2008a;Kaplan et al, 2008;Li et al, 2008a;Du et al, 2011;Khan et al, 2011;Thomas et al, 2011;Hu et al, 2012;Radhakrishna et al, 2012). These mutations include missense, nonsense, splicing mutations, insertions, and deletions.…”
Section: Discussionmentioning
confidence: 99%
“…9 To date, 44 FRMD7 gene mutations have been identified in various NYS families suggesting that this gene has an important role in the NYS development. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The majority of these mutations were clustered in the highly conserved FERM-C domain in exons of 7-9 ( Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with a previously published report. 25 The clinical significance of hemi/homozygous as compared with heterozygous mutation is not yet known, although Kaplan et al 13 found a missense mutation, R229G, in the FRMD7 gene in heterozygous and homozygous condition in members of a large X-linked NYS family without phenotypic variation. The location of the present residues is highly conserved in multiple species (Figure 1c) suggesting that the mutation at codon 305 is likely to have a significant effect on FRMD7 protein functionality.…”
Section: Resultsmentioning
confidence: 99%